Health Behaviours and Spine Pain among Nursing Staff - Renata Jabłońska; Ewelina Strączek; Paweł Sokal (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Diseases of the musculoskeletal system are often caused by long-term and often simultaneous influence of the work environment and individual physical factors of each human being. Healthcare workers are most at risk of suffering from musculoskeletal pain. Aim. Assessment of health behaviours and back pain among professionally active nursing team. Material and Methods. 123 active nurses participated in the study. The method of diagnostic survey was used, using standardized research tools: VAS pain scales, Oswestry questionnaire, IZZ questionnaire. Results. According to the conducted analysis, 79.7% of people experience pain; 17.1% reported ailments on an average level. The highest results were obtained by the respondents in terms of questions concerning a positive mental attitude (average value: 3.45 ± 0.59), and the lowest in terms of health practices (average value: 2.89 ± 0.64). In the case of questions about preventive behaviours, women had statistically significantly (p = 0.010) higher results than men. Conclusions. Pain in the spine concerns the majority of the surveyed nurses. In terms of their own health behaviours, the respondents paid the least attention to proper health habits. There was no correlation in pain, functional capacity and personal health behaviour. (JNNN 2021;10(4):135–143)